The authoritarian surveillant assemblage: Authoritarian state surveillance in Turkey. (October 2019) - Topak, Özgün E
This article examines Turkey's authoritarian state surveillance regime by developing the concept of the authoritarian surveillant assemblage (ASA), building on and expanding the concept of the surveillant assemblage (SA). Turkey's ASA is the outcome of diverse surveillance systems, which continuously expand their reach, form new connections and incorporate new actors. These systems include a protest and dissent surveillance system, an internet surveillance system, a synoptic media surveillance system and an informant–collaborator surveillance system. Turkey's ASA is controlled by the Turkish state and serves its repressive interests. Although pivotal in emphasizing the complexity of surveillance connections and increasing diversification of and collaboration among surveillance actors, the SA model of surveillance puts the main emphasis on decentralized, uncoordinated and multifaceted forms of surveillance, and does not offer sufficient analytical space to understand how an authoritarian state could coordinate diverse surveillance systems and use it for the overarching purpose of control. The article draws on Michael Mann's theory of state power and the authoritarian state to address these limitations of the SA and conceptualize the ASA. It shows how the diverse systems of Turkey's ASA work in concert with one another under the hierarchical command of Erdoğan's Justice and Development Party (AKP) to control the population and suppress dissent.